Badantam Traditions in Marriage in Korong Koto Rajo Nagari Sunur Tengah, Nan Sabaris District, Padang Pariaman Regency - Sosa, Sosa Hijria Audia; Suharti; Yurisman (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
This thesis is entitled "Badantam Traditions in Marriage in Korong Koto Rajo Nagari Sunur Tengah, Nan Sabaris District, Padang Pariaman Regency". The purpose of this study was to find out the background to the emergence of the Badantam tradition and the function of the Badantam tradition in Korong Koto Rajo Nagari Sunur Tengah, Nan Sabaris District, Padang Pariaman Regency. The theory used in this final project is Malinowski's theory of functionalism. The method that the writer uses is a qualitative method, with data collection techniques namely observation, interviews and documentation. The results of the study found that the background to the emergence of the Badantam tradition was economic limitations. Due to the low economic status of the community, this led to the birth of the Badantam in the life of the Korong Koto Rajo Nagari Sunur Tengah community which aims to help with the cost of carrying out the wedding. The functions of this Badantam tradition are as follows: 1) economic function, 2) function as a gathering place, 3) function of cultural inheritance.